ANALISIS PEMAHAMAN MATEMATIKA SISWA DITINJAU DARI MINAT BELAJAR PADA MASA PANDEMI COVID-19 - Vina Dwi Sri Dewi Ritonga; Roslian Lubis; Nunik Ardiana (JURNAL MathEdu (Mathematic Education Journal), 2021)
This study aimed to analyze students’ mathematical comprehension based on learning interest in pandemic Covid-19 period. The approach of the research applied qualitative descriptive. Questionnaire, test, and interview were used in collecting the data. The technique of data analysis used data reduction, presentation of the data, and taking conclusion. Subject of the research was categorized into 3 part includes students who have students’ high learning interest, students’ average learning interest , and students’ low learning interest. Furthermore, the result of the research shows (1) students who have high learning interest have high mathematical comprehension, (2) students who have average learning interest have average mathematical comprehension, and (3) students who have low learning interest have low mathematical comprehension.